Estudio de la rentabilidad en la MGCENTRODCAPACITACION S.A. de la ciudad de Guayaquil en el periodo 2022. - Cedeño Acosta, María José (2024)
Profitability is a key indicator to evaluate the success and viability of a business. Its study is of vital importance since it allows us to know if the profitability shown by a company is generating profits and if it is capable of efficiently using its resources to obtain a return. positive of the investment. Here we will address a study on the profitability of MGCENTRODCAPACITACION S.A, having identified that as a form of business development it intensifies the effort in the current activity of the company. with the aim of covering its expansion process nationwide. Evaluating profitability as such is knowing its performance in comparison with its competitors and with its own financial objectives and goals. It also allows the company to adapt to a constantly changing market, cover trends and customer needs, adjust your approach and products to meet these changing demands.